Parenting Perceptions of Low-Income Mothers. Issue 2 (March 2015) - Webb, Jenny; Morris, Melanie Hall; Thomas, Sandra P.; Combs-Orme, Terri
Abstract Purpose: The purpose of this descriptive qualitative study was to gain understanding of perceptions of low-income pregnant women and mothers about parenting. Study Design and Methods: Participants were 65 low-income, primarily African American, women in their 20s and 30s who were recruited from a faith-based social service center in Memphis, Tennessee. Interviews were conducted by nursing, social work, and psychology students. The existential phenomenological method was used to analyze verbatim responses of participants to vignettes depicting parenting behaviors of hypothetical mothers. Results: Five global themes were identified: (a) Focus on baby's development: "Because I'm the Mother, I'm the First Teacher"; (b) Focus on baby's safety/security: "The Baby Could Be Hurt"; (c) Focus on conveying love: "She Just Wants the Baby to Feel Her Love"; (d) Focus on learning the rules of good childcare: "It's Important to Know the Do's and Don'ts"; and (e) Focus on doing it differently (better) than parents did: "When You Know Better, You Do Better." Clinical Implications: Findings suggest that these mothers care deeply about providing a better life for their children than the life they have had. They desire to learn about being the best parents they can be. As nurses, we can help to provide educational opportunities for mothers through a variety of evidence-based interventions delivered across the childbearing years.